Analisis Faktor-Faktor Penyebab Piutang Tak Tertagih Dan Upaya Penanggulangan Serta Penyelesaiannya Pada PT BPR Tataarta Swadaya Kota Gajah - Adelia, Adelia; Zanaria, Yulita; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the internal factors, external factors causing bad debts and efforts to resolve them at PT. BPR Tataarta Swadaya Kota Gajah. The type of research used is descriptive qualitative research. The instruments used in this study are interviews and observations. Data analysis was carried out using the Miles and Huberman data analysis model. The results of the study indicate that internal factors are factors originating from within the company (BPR Tataarta Swadaya Kota Gajah as the creditor are: Weak credit administration system, Weak credit information system and Deviations in the implementation of credit granting procedures External factors causing bad debts are factors originating from outside the company in this case are Fostered Partners who receive capital loans from BPR Tataarta Swadaya Kota Gajah consisting of Fostered Partners experiencing a decline in economic conditions, Debtor business failure and Debtors running away.